Design and analysis of discrete PID controller for Luo converter. (19th March 2020) - Shenbagalakshmi, R.; Vijayalakshmi, S.; Geetha, K.
A thorough and effective analysis of the positive output super lift Luo converter along with the discrete PID controller has been carried out. The converter is designed to operate under continuous conduction mode and modelled using state space averaging method. The closed loop control is based on time domain approach and current mode discrete PID controller thus, designed tunes the system in such a way that the converter specifications are satisfied. The Luo converter along with the controller thus designed is robust, shows stiff output voltage regulation without any overshoots or undershoots and highly efficient. The steady state error is almost zero. Extensive simulation is carried out and the results are illustrated. The controller platform is verified using LabVIEW.